ANALYSIS OF INTERLEUKIN-10 LEVELS IN MESENCHYMAL STEM CELL SECRETOME CREAM WITH ELISA METHOD - Amelia, Vika; Marlina; Sudji, Ikhwan Resmala (BRIN - Badan Riset dan Inovasi Nasional, 2023)
Mesenchymal Stem Cells (MSC) are cells that are able to differentiate into other cells and have immunomodulatory properties that are used to treat inflammatory diseases. MSCs have the ability to repair damaged tissue by regenerating damaged tissue. MSCs produce a secretome, where the MSC secretome has various cytokines, chemokines, growth factors, anti-inflammatory factors and proteins that are produced in molecular form. One of the molecules secreted by the secretome is Interleukin-10.IL-10 is an anti-inflammatory cytokine which functions to inhibit the production of several other types of cytokines such as TNF, IL-1, chemokine and IL-12). Apart from that, IL-10 is able to inhibit the function of macrophages in assisting T cell activity. One of the products from Secretome MSC is a cream preparation. To find out whether the MSC cream contains IL-10 protein, Interleukin-10 levels were analyzed in the MSC secretome cream with 3 different MSC cream concentration formulations (2%, 3% and 5%). Analysis of IL-10 levels was carried out using ELISA to detect IL-10 antigen. The results of the examination of 9 samples showed that all samples were positive for IL-10 with a concentration of 2% dilution 1:2 showing the best results with an Optical Density (OD) of 0.069 and followed by a concentration of 5% dilution 1:2 showing an OD value of 0.065.